Genius Learning and Think Talk Write Reviewed from Junior High School Students’ Creativity - Adi Ari Wibowo; Mohamad Rif'at; Ahmad Yani (Universitas Tanjungpura, 2020)
The study aimed to obtain information about comparing student learning outcomes, given the genius learning strategy and think talk write in terms of student creativity. The study was a quasi-experimental design and the research design was a 2x3 factorial design. The population in this study were all students of VIII grade at SMP Negeri 1 Sepauk, with a sample of VIIIC and VIIID grades who were randomly selected using cluster random sampling technique. Based on the results of data processing, the following conclusions were obtained: (1) The learning outcomes between students who were given a genius learning strategy were relatively the same as think talk write, both in general and based on the student's creativity category, (2) The learning outcomes between students who had relatively high creativity the same as students who have medium or low creativity, and students with moderate creativity have relatively the same learning outcomes as students who have low creativity both in general and in terms of learning strategies. Keywords: Creativity, Genius Learning, Think Talk Write